The potential influence of hormesis on evolution of resistance to herbicides - Belz, Regina G.; Carbonari, Caio A. [UNESP]; Duke, Stephen O. (Elsevier, 2022)
Hormesis is a common response of both herbicide-susceptible and herbicide-resistant plants to herbicides. Herbicide resistance in weeds is rapidly evolving, and although little studied, there is growing evidence that hormesis plays a role in the changes in sensitivity of weed populations to herbicides. This can occur in susceptible weed populations in which hormesis favors a subpopulation of more vigorous plants. At recommended application doses for weed control, a hormetic dose is likely to favorably influence a significant proportion of the herbicide-resistant weeds, enhancing their propagation and spread.
Keywords: Dose; Glyphosate; Iodosulfuron-methyl; Pesticide; Population; Weed